An in vitro tumor swamp model of heterogeneous cellular and chemotherapeutic landscapes. Issue 14 (18th June 2020) - Lin, Ke-Chih; Sun, Yusha; Torga, Gonzalo; Sherpa, Pema; Zhao, Yihua; Qu, Junle; Amend, Sarah R.; Pienta, Kenneth J.; Sturm, James C.; Austin, Robert H.
Abstract : A microfluidic platform was developed that generates a gradient of chemotherapy via diffusion to study evolutionary dynamics of cancer. Abstract : The heterogenous, highly metabolic stressed, poorly irrigated, solid tumor microenvironment – the tumor swamp – is widely recognized to play an important role in cancer progression as well as the development of therapeutic resistance. It is thus important to create realistic in vitro models within the therapeutic pipeline that can recapitulate the fundamental stress features of the tumor swamp. Here we describe a microfluidic system which generates a chemical gradient within connected microenvironments achieved through a static diffusion mechanism rather than active pumping. We show that the gradient can be stably maintained for over a week. Due to the accessibility and simplicity of the experimental platform, the system allows for not only well-controlled continuous studies of the interactions among various cell types at single-cell resolution, but also parallel experimentation for time-resolved downstream cellular assays on the time scale of weeks. This approach enables simple, compact implementation and is compatible with existing 6-well imaging technology for simultaneous experiments. As a proof-of-concept, we report the co-culture of a human bone marrow stromal cell line and a bone-metastatic prostate cancer cell line using the presented device, revealing on the same chip a transition in cancer cell survival as a function of drug concentration on the population level while exhibiting an enrichment of poly-aneuploid cancer cells (PACCs) as an evolutionary consequence of high stress. The device allows for the quantitative study of cancer cell dynamics on a stress landscape by real-time monitoring of various cell types with considerable experimental throughput.